Formulasi Sediaan Facial Wash Dari Ekstrak Etanol Kulit Pisang Raja (Musa Paradisiaca L.) Secara In Vitro - Julianty, Siti Muliani; Nadia, Syarifah; Yushfi, Melza Rizqan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Banana peel (Musa paradisiaca L.) has long been known to have various substances that are beneficial to health. The use of ethanol extract as a solvent also shows great potential to extract bioactive compounds from natural ingredients. One of the most common skin care products used in the skin care industry is Facial Wash. This product is made to cleanse and care for facial skin, such as acne control, anti-aging, or other skin care. This study aims to make a facial wash preparation with active ingredients from natural ingredients, so that it is rational to use as a facial cleanser. The basic facial wash is made first with a mixture of facial wash bases formulated into 4 formulas with varying concentrations. Evaluation of the preparation includes organoleptic tests, homogeneity, pH, spreadability, and irritation tests. All formulas with various homogeneous concentrations, pH 6 - 8, are stable in storage for 8 weeks. The results of the spreadability test meet the requirements of 5-7 cm, the average viscosity ranges from 30.7-34 cPs, the average foam height ranges from 4.0 - 6.2 cm and the results of the irritation test show that it does not cause irritation to the volunteer's skin.